Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Appendix G - Complex Numbers - G Exercises: 14



Work Step by Step

We use basic root properties to simplify ($\sqrt{a}\sqrt{b}=\sqrt{ab}$): $\sqrt{-3}\sqrt{-12}$ $\sqrt{3*-1}\sqrt{12*-1}$ $=\sqrt{3}i\sqrt{12}i$ $=\sqrt{3*12}i^{2}$ We use the fact that $i^2=-1$ (because $i=\sqrt{-1}$) $=\sqrt{36}*-1$ $=-6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.